SIMULASI PENGONTROLAN DAN MONITORING ALIRAN MINYAK DENGAN MENGUBAH KECEPATAN POMPA - Indra Roza; Teguh Vikriandi Tarigan; Ervin Panggabean (Jurnal Simetri Rekayasa, 2020)
With the development of technology, then every industry is eager to make tools that can help employees and industrial management, one of which is a tool in the field of control. In the world of palm oil industry, oil control is needed to control the flow of oil to the plant. With automatic oil control, the oil flow rate to the plant can be controlled according to the needs of the plant. Currently there are still many palm oil industries that have not controlled the oil flow pump automatically. Although the industry includes a large industry, it still uses manual control. Then comes the idea to design the pump control automatically by using PLC. Here the test by raising and lowering the frequency for motor pump speed can change. From the test results that have dilakuakan can be concluded that a pump that is given a frequency greater than the frequency given by PLN, then the pump speed will increase according to the given by the PLN, then the pump speed will decrease according to the frequency given by the inverter. But if the pump is given a frequency smaller than the frequency frequency given by the inverter. In the simulation of controlling and monitoring the flow of oil by changing the speed of the pump can be applied in the industry, because the control in this way is very simple and can be applied in the palm oil industry